(untitled) (American Journal of Education and Technology, 2023)
Sustainable development is dependent on the social, cultural, and environmental setting. Authentic learning materials should be designed with real-world applicability outside of the classroom. This study aimed to investigate the locally available ethno-learning resources for teaching biology to promote sustainable development education in the district of Esperanza, particularly in Esperanza Districts I and II. The study employed a descriptive-quantitative approach emphasizing a descriptive research design where the data gathered from the teacher-respondents was recorded and described descriptively. A complete enumeration has been utilized in the study to procure all the teachers in the said locale. Microsoft Excel was used to analyze teacher-respondents’ data and create graphs and tables. Books, modules, supplementary reading materials, laboratory apparatuses, and laptops are both districts’ main instructional learning resources, while speakers, projectors, and TVs are the least technology-based. The most common problems encountered by science teachers are the inadequate number of books, the inadequate number of projectors and computers, and other technology-based resources. Also, indigenous resources, realia, and replicas under localized learning materials are the most effectively used by teachers in teaching science. Future studies should highlight the importance of localized and contextualized materials in teaching science, create more locally available materials, compare learning materials locally and internationally, and use other relevant methods to ensure the availability of learning resources.